1991
DOI: 10.1002/cne.903070312
|View full text |Cite
|
Sign up to set email alerts
|

Cell migration in the rat embryonic neocortex

Abstract: Three-dimensional reconstructions of the normal rat embryonic (E) neocortex on days E15, E17, E19, and E21, using Skandha (software designed by J. Prothero, University of Washington, Seattle), show that the neocortical ventricular zone shrinks rapidly in the medial direction during cortical morphogenesis. [3H]thymidine autoradiography indicates that the shrinkage of the ventricular zone occurs before neurons in lateral and ventrolateral parts of layers IV-II are generated. Consequently, most of these neurons o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
94
1
3

Year Published

1994
1994
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(107 citation statements)
references
References 26 publications
9
94
1
3
Order By: Relevance
“…The neuroepithelium of olfactory bulb also was labeled. At this stage labeling appeared as a band becoming thinner than previously, because the cortical ventricular zone of the neuroepithelium also had become thinner (Bayer and Altman, 1991). Labeling in Purkinje cell plate also appeared stronger and more extended.…”
Section: Late Gestational Development (E17-e19)mentioning
confidence: 66%
See 1 more Smart Citation
“…The neuroepithelium of olfactory bulb also was labeled. At this stage labeling appeared as a band becoming thinner than previously, because the cortical ventricular zone of the neuroepithelium also had become thinner (Bayer and Altman, 1991). Labeling in Purkinje cell plate also appeared stronger and more extended.…”
Section: Late Gestational Development (E17-e19)mentioning
confidence: 66%
“…Labeled cells appeared as clusters in a 100-m-thick band lining the ventricle (Fig. 4 E), corresponding to the synthetic and mitotic zones of the neuroepithelium, as evidenced by Bayer and Altman (1991) with the use of [ 3 H]thymidine labeling, whereas the differentiating field was labeled only very scarcely. This shows that D 3 R-expressing cells are proliferative and not postmitotic differentiating cells.…”
Section: Late Gestational Development (E17-e19)mentioning
confidence: 98%
“…This angle is believed to mark the border between the ventricular zones of the developing neocortex and the striatum (Smart and Sturrock, 1979). It has been shown that neurons generated along the dorsal bank of the caudatopallial angle migrate ventrolaterally toward the lateral isocortex following the guidance ofthe radial glial fibers (Smart and Sturrock, 1979;Bayer et al, 1991;Misson et al, 1991a). Nevertheless, what is revealed by the TuJl immunostaining within the proliferative zones surrounding the angle are not cells directed ventrolaterally, but dorsomedially, perpendicular to the directions of the radial glial processes of this area (Misson et al,199 la).…”
Section: Resultsmentioning
confidence: 99%
“…The combination of two detection markers allowed us to evaluate both the amount of new neurons generated 10 -14 d before the animal was killed, by the overall expression of the immature neuronal marker DCX (Bayer et al, 1991), as well as the number of neuroprogenitors emerging during the concurrent BrdU/GA injection period (those that differentiated into the neuronal lineage and thus presented BrdU/DCX dual staining). Both systems gave comparable results as to the effect of the pathological process of EAE and that of GA treatment.…”
Section: Discussionmentioning
confidence: 99%